Influence of implant protrusion length on non-grafting osteotome sinus floor elevation with simultaneous implant: a 3- to 9-year retrospective study - Yi Yu; Qiming Jiang; Zhengchuan Zhang; Xiaolin Yu; Feilong Deng (SpringerOpen, 2021)
Abstract Background This study analyzed the influence of implant protrusion length (IPL) on the possible factors that affect the long-term outcomes utilizing non-grafting osteotome sinus floor elevation (OSFE) with simultaneous implant placement, and to explore the optimal range of IPL. Materials and methods A retrospective study design was adopted. The clinical and radiographic data of 105 implants in 65 patients were collected after 3-9 (mean 5.04) years follow-up. IPL was divided into three groups (group1, IPL<2mm; group2, 2mm≤IPL<4mm; group3, IPL≥4mm). Endo-sinus bone gain (ESBG), peri-implant marginal bone loss (MBL), bone to implant contact length (BICL), and percentage of ESBG (%ESBG) were used to evaluate non-grafting OSFE. A Kaplan-Meier analysis was performed to assess the cumulative survival rate. Multiple linear regression model was used to explore the relationship between the possible influence factors and ESBG. Analysis of variance (ANOVA) was applied to explore the correlation of IPL with ESBG, MBL, BICL, and %ESBG. Results A total of 102 implants in 62 patients fulfilled the survival criteria, giving the cumulative survival rates of 96.4% and 94.1% for implant-based analysis and patient-based analysis, respectively. The mean ESBG, MBL, and BICL at the latest follow-up were 1.95±0.88 mm, 0.58±0.68 mm, and 5.51±1.47 mm. ESBG was found to be positively correlated to IPL. A significant decreased bone formation efficiency was found when IPL was over 4 mm (P=0.02). Conclusions An optimal range of IPL within 4 mm was recommended for better long-term outcomes when applying non-grafting OSFE with simultaneous implant placement.